Pengaruh Leverage, Capital Intensity, dan Profitabilitas Terhadap Tax Avoidance - Intan Sonia Apriani; Sunarto Sunarto (Universitas Sains dan Teknologi Komputer, 2022)
This study aims to analyze the effect of leverage, capital intensity, and profitability on tax avoidance. The population used in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020. Sampling using purposive sampling technique and found 75 observations. This secondary data was analyzed using software evaluations 9. The results of the study show that leverage has no effect on tax avoidance, capital intensity has no effect on tax avoidance, and profitability has a negative effect on tax avoidance.